The Impact of Early-Life Exposure to Antimicrobials on Asthma and Eczema Risk in Children - Jackson-Browne, Medina S. (Curr Environ Health Rep, 2019)
PURPOSE OF REVIEW: We examined recent research on associations of prenatal and early-childhood exposure to the antimicrobial compounds, triclosan, and parabens, with the risk of asthma and eczema in children. We will discuss potential biological mechanisms of this association and highlight strengths and limitations of the study design and exposure assessment of current findings. RECENT FINDINGS: Results of available toxicological and epidemiologic studies indicate a potential link of triclosan and paraben exposures with asthma and eczema in children, as well as changes in microbiome diversity and immune dysfunction, which could possibly mediate an association with the health outcomes. SUMMARY: A small number of studies suggest that triclosan and paraben exposures could be related to the risk of asthma and eczema in children. Although current findings are far from conclusive, there is emerging evidence that changes in microbiome diversity and immune function from antimicrobial exposure may mediate these relations.